Crime Map Book - Tarmiji, Masron; Azizul, Ahmad; Norita, Jubit; Mohd Hafizuddin, Sulaiman; Ruslan, Rainis; Mohd Sofian, Redzuan; Syahrul Nizam, Junaini; Mohd Azizul Hafiz, Jamian; Asykal Syakinah, Mohd Ali; Mohamad Suhaidi, Salleh; Farah, Zaini; Ryoji, Soda; et al. (Centre for Spatially Integrated Digital Humanities, Faculty of Social Sciences and Humanities Universiti Malaysia Sarawak (UNIMAS), 2024)
Crime is a pervasive social phenomenon that profoundly impacts the well-being and security of communities. As such, crime mapping has emerged as a vital tool for understanding the spatial distribution and patterns of criminal activities within specific areas. This Crime Map Book offers a comprehensive analysis of crime patterns across key regions in Malaysia, utilising Geographic Information System (GIS) technology alongside crime data collected between 2015 and 2020. The study integrates advanced spatial statistical methods, including Getis-Ord Gi*, Emerging Hot Spot Analysis (EHSA - Space-Time Pattern Mining), Standard Deviational Ellipse (SDE - Directional Distribution), Mean Center, Local Indicators of Spatial Association (LISA), Buffer Analysis, Location Quotient Analysis, and Kernel Density Estimation. These techniques provide a multi-faceted approach to crime analysis, enabling a more nuanced understanding of criminal trends and facilitating the development of geographically informed crime prevention strategies. This body of work holds significance not only for law enforcement, who can leverage these insights to refine their strategies and resource allocation, but also for urban planners and security professionals tasked with designing safer environments. The data utilised in this study is drawn from multiple sources, including the Bukit Aman Criminal Investigation Department and various governmental agencies responsible for land use data. By presenting a series of maps that illustrate crime patterns across diverse categories and demographics, this book aims to influence future crime prevention efforts. The findings offer crucial insights for managing risks and enhancing security in identified crime hotspots.